+0  
 
+1
475
1
avatar

(2,87 * 10-6) * (0,32 * 10-6) * (0,013 * 10-6) = ?

 12.10.2017
bearbeitet von Gast  12.10.2017
 #1
avatar+8 
+1

Hey, also

 

 

\((2,87 * {10}^{-6}) * (0,32 * {10}^{-6}) * (0,013 * {10}^{-6}) \)
 \( = 2,87 * 0,32 * 0,013 * {{10}^{-6}}^{3} \)

\( = 0,0119392 * {10}^{(-6*3)} \)

\( = 0,0119392 * {10}^{-18} \)

\( = 0,0119392 * 0,000000000000000001\) (17 nullen nach dem Komma, bevor die 1 folgt)
\(= 0.0000000000000000000119392\) (19 nullen nach dem Komma, bevor die 1 folgt)


Liebe Grüße Einszig

 12.10.2017

11 Benutzer online

avatar